Pedagogy in practice: a qualitative exploration of English language teaching (ELT) for graduate school using narrative inquiry, instructional material analysis, and observational inquiry - Eslit, Edgar R. (Frontiers in Education, 2025)
IntroductionEnglish Language Teaching (ELT) in multilingual graduate classrooms in the Philippines presents pedagogical, linguistic, and institutional complexities that transcend prescriptive models. In regions like Mindanao, where post-conflict reconstruction and linguistic plurality converge, instructors often navigate ELT through improvisation, relational scaffolding, and material adaptation. This study responds to the need for a grounded exploration of graduate ELT as a lived, context-sensitive practice.MethodsGuided by a multi-theoretical framework—Postmethod Pedagogy, Sociocultural Theory, Critical Pedagogy, Multimodal Theory, Actor-Network Theory, and Activity Theory—the study employed narrative inquiry, instructional artifact analysis, structured classroom observation, and Orange-assisted visualization. Twenty purposively selected graduate instructors and students from St. Michael's College of Iligan, Inc. (SMCII) participated during AY 2024–2025. Data were thematically analyzed using Braun and Clarke's six-phase framework, with trustworthiness reinforced through member checking, peer debriefing, and triangulation.ResultsTen core themes emerged: (1) strategic pedagogical improvisation, (2) instructional materials as scaffolds and filters, (3) learner identity and linguistic anxiety, (4) observed communicative exchanges, (5) evolving pedagogical identity, (6) digital mediation and multimodal engagement, (7) peer dynamics and collaborative language construction, (8) lexical density and semantic awareness, (9) instructional tensions between coverage and depth, and (10) feedback culture and constructive mediation. Orange visualizations affirmed thematic convergence and lexical clustering, supporting interpretive depth without flattening narrative nuance.DiscussionFindings affirm graduate ELT as a relational, adaptive, and ideologically charged practice. Instructors act as designers and co-learners, while students bring sociolinguistic trajectories that reshape pedagogy in real time. The study highlights the need for inclusive material design, dialogic feedback, and flexible curriculum frameworks that honor linguistic diversity and emotional nuance. Orange visualization proved valuable in mapping pedagogical rhythms and thematic density, though limited in capturing affective tone.